Kecemasan Guru Honorer Terhadap Perbedaan Status dengan Guru PNS/PPPK di Lingkungan Sekolah - Muhammad Dzaki Fadhilla; Kamalia Kamalia (Journal of Society Counseling, 2026)
This study aims to deeply understand the anxiety experienced by honorary teachers due to the difference in employment status with civil servant/PPPK teachers at SMK Negeri 4 Medan City. This study uses a descriptive qualitative approach, which focuses on the subjective experiences of informants. Data was obtained through in-depth interviews, observations, and documentation. Informants were selected using a purposive sampling technique with the criteria of honorary teachers who are still actively teaching, have at least one year of work experience, and interact directly with civil servant/PPPK teachers. Data were analyzed using Miles and Huberman's interactive model which included data reduction, data presentation, and conclusion drawn. The validity of the data was tested through source triangulation and member check. The results showed that the anxiety of honorary teachers has varying degrees, ranging from mild to complex, which are influenced by attachment to the profession and the way individuals interpret working conditions. The main factors that cause anxiety include low welfare, uncertainty of employment status, and social comparison with civil servant/PPPK teachers. The impact of anxiety on performance also varies, where in some conditions anxiety can be a motivation, but in other conditions it can decrease work morale. These findings show that the anxiety of honorary teachers is the result of an interaction between structural, psychological, and social factors, so it requires more comprehensive attention.